Personal management in the Malaysian army: a review / Halim Hariri - Hariri, Halim (Faculty of Law, 1982)
Personnel management is the central pervasive subsystem of all organisations. It is becoming apparent to an increasing number of executives that people rather technology determine the success or failure of organisations, however systems of personnel management are variable and are influenced by factors such as environment, organisation, profession, situation and time. In the Army every officer is a manager, without systematic means of managing men and resources under complex and diverse conditions an officer has little chance of success. This is because in warfare, the effectiveness of all available men and equipment must be maximised. The present system of personnel management in the Malaysian Army is predominantly autocratic or authoritative in nature. Such a system is most suitable in combat or emergency situations, when time is overriding. The system inspite of its weaknesses have worked well in the past. However with the changing of time there is now a compelling need to review it. The democratic and laissez-faire approach can be adopted but will only be suitable in certain situations an environment.